2019
DOI: 10.1177/2047487319869694
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of interleukin 6 trans-signalling in middle-aged men and women at low-intermediate risk of cardiovascular events

Abstract: Background Interleukin 6 trans-signalling is independently associated with the risk of cardiovascular events. The aim of this study was to investigate if interleukin 6 trans-signalling can identify individuals at risk for cardiovascular events (coronary artery disease and ischaemic stroke) among those at-low–intermediate risk. Methods In a cohort of 60-year-olds ( n = 4232, incident cardiovascular events n = 525), interleukin 6 trans-signalling was estimated by a ratio between the pro-inflammatory interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 196 publications
(299 reference statements)
3
7
0
1
Order By: Relevance
“…The current 15 and previous observations 9 of Ziegler et al add important information about the participation of IL-6 in ASCVD, and suggest that measurement of this cytokine pathway can give prognostic information. Despite the fact that CRP levels were not measured, the incorporation of B/T to a model including IL-6 levels, which modulates the classic signaling pathway, suggests that trans-signalling brings additional discriminatory information to the latter.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…The current 15 and previous observations 9 of Ziegler et al add important information about the participation of IL-6 in ASCVD, and suggest that measurement of this cytokine pathway can give prognostic information. Despite the fact that CRP levels were not measured, the incorporation of B/T to a model including IL-6 levels, which modulates the classic signaling pathway, suggests that trans-signalling brings additional discriminatory information to the latter.…”
supporting
confidence: 68%
“…Finally, the possible elevated costs of the B/T complex determination should be considered as a barrier for its implementation in preventive cardiology practice. At any rate the studies of Ziegler et al 9,15 add important confirmatory information for the participation of IL-6 on atherogenesis. Whether specific inhibitors of IL-6 trans-signalling 18 may reduce ASCVD events and could add to benefits shown by upstream interleukin-1b inhibition as shown in CANTOS 8 remains to be determined.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The involvement of inflammation besides LDL in atherosclerosis has been recently proven in the proof-of-concept CANTOS (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) trial, showing that interleukin 1β inhibition resulted in a 15% reduction in cardiovascular events [12]. Supporting these findings, it has been recently observed that interleukin 6 trans-signaling increases the risk of cardiovascular events [13]. Interleukin 1β/ interleukin 6 signaling is activated by the nucleotide-binding leucine-rich repeat-containing pyrine receptor 3 (NLRP3) inflammasome platform [14].…”
Section: Atherosclerosis: Lipids and Inflammationmentioning
confidence: 81%